If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 1) = 4x + -8 Reorder the terms: 5(1 + x) = 4x + -8 (1 * 5 + x * 5) = 4x + -8 (5 + 5x) = 4x + -8 Reorder the terms: 5 + 5x = -8 + 4x Solving 5 + 5x = -8 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 5 + 5x + -4x = -8 + 4x + -4x Combine like terms: 5x + -4x = 1x 5 + 1x = -8 + 4x + -4x Combine like terms: 4x + -4x = 0 5 + 1x = -8 + 0 5 + 1x = -8 Add '-5' to each side of the equation. 5 + -5 + 1x = -8 + -5 Combine like terms: 5 + -5 = 0 0 + 1x = -8 + -5 1x = -8 + -5 Combine like terms: -8 + -5 = -13 1x = -13 Divide each side by '1'. x = -13 Simplifying x = -13
| (6/5x-15)+1=-(8/x-3) | | 20.3x=20(x+.00568) | | 20.3x=20(x+.007) | | 10=t(t-9) | | 21x=20(x+.007) | | 21x=20(x+.07) | | w^3=28 | | y^2-125=0 | | X-4+(2X/5)=-4+(7X/5) | | -39-(-23)=x | | 21x=20(x+.0047) | | u^2+3u-6=0 | | 7+3(5)+16= | | (X/3)+6=(1/15) | | 7x+4=-3(x-6) | | (3/4)-(X/12)=1 | | 60(x+.10)=75x | | 4-(3X/5)=1-(X-3) | | 60(x+.5)=75x | | .3x-.8-44=1 | | 18a+12=84 | | 8-4x=2-7k | | -5(-10+3x)=-85 | | x-8x=21+28 | | 6+9(X-2)=13X-4(X+4) | | 4x^3-6x^2-24x+8=0 | | 4x^2-11X-3/9-x^2 | | 23x=20(x+.0047) | | -(3X-7)+1=5X+8(1-X) | | -(8h-w)= | | 2X-4(X+1)=-2X+23 | | -(-5m+4n-8p)= |